More pi, please : what drives the formation of unsaturated molecules in the interstellar medium? (2025)
We present a computational investigation into the fragmentation pathways of ethanolamine (C2H7NO, EtA), propanol (C3H8O, PrO), butanenitrile (C4H7N, BuN), and glycolamide (C2H5NO2, GlA)—saturated organic molecules detected in the interstellar medium (ISM), particularly in the molecular cloud complex Sagittarius B2 (Sgr B2) and its molecular cloud G+0.693–0.027. Using electron-impact ionization data and Born–Oppenheimer molecular dynamics simulations, we investigate how cosmic rays, cosmic-ray-induced UV fields, and shock-induced heating can induce the fragmentation of these molecules, resulting in the formation of unsaturated species with extended pi-bond networks. Despite the attenuation of external UV radiation in G+0.693–0.027, these energetic processes are capable of driving partial transformations of saturated into unsaturated molecules, supporting the coexistence of species like EtA and GlA alongside unsaturated nitriles such as cyanoacetylene (HC3N), cyanopropyne (CH3C3N), and cyanoallene (CH2CCHCN). Our findings underscore the significance of high-energy mechanisms in enhancing chemical complexity within molecular clouds and offer insights into the pathways that govern the evolution of organic molecules in the ISM.